Impact of air exposure and annealing on the chemical and electronic properties of the surface of SnO2 nanolayers deposited by rheotaxial growth and vacuum oxidation - Kwoka, Monika; Krzywiecki, Maciej (Beilstein Journal of Nanotechnology, 2017)
In this paper the SnO2 nanolayers were deposited by rheotaxial growth and vacuum oxidation (RGVO) and analyzed for the susceptibility to ambient-air exposure and the subsequent recovery under vacuum conditions. Particularly the surface chemistry of the layers, stoichiometry and level of carbon contamination, was scrutinized by X-ray photoelectron spectroscopy (XPS). The layers were tested i) pristine, ii) after air exposure and iii) after UHV annealing to validate perspective recovery procedures of the sensing layers. XPS results showed that the pristine RGVO SnO2 nanolayers are of high purity with a ratio [O]/[Sn] = 1.62 and almost no carbon contamination. After air exposure the relative [O]/[Sn] concentration increased to 1.80 while maintaining a relatively low level of carbon contaminants. Subsequent UHV annealing led to a relative [O]/[Sn] concentration comparable to the pristine samples. The oxidation resulted in a variation of the distance between the valence band edge and the Fermi level energy. This was attributed to oxygen diffusion through the porous SnO2 surface as measured by atomic force microscopy.
Keywords: Fermi level position; RGVO nanolayers; rheotaxial growth and vacuum oxidation (RGVO); surface chemistry; tin-oxide electronics; X-ray photoelectron spectroscopy (XPS)